Characterization of cryorolled low carbon steel using ferrite-martensite starting microstructure - Abu Seman, Anasyida; Zakaria, Siti Aminah; Ahmad, Muhammad Syafiq; Hussain, Zuhailawati; Dhidaw, Brij Kumar; Taiwo Ebenezer Abioye, Taiwo Ebenezer (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Cryo-rolling, a technique of severe plastic deformation (SPD) performed at cryogenic temperatures, has proven to be a promising technique for improving the microstructure and mechanical properties of low-carbon steels. Low carbon steel with a two-phase ferrite-martensite starting microstructure was subjected to cryogenic rolling at liquid nitrogen temperature to produce sheets with different deformation rates: 50%, 70%, and 90%. The microstructure, mechanical properties, and corrosion resistance were investigated. The results show that cryo-rolling effectively refines the microstructure and leads to a higher dislocation density and smaller grain size as the deformation rate increases. The cryo-rolled sample deformed at 90% has the highest grain aspect ratio (35.5), the smallest crystallite size (13.70 nm), the highest lattice strain (74.6 x 10-3), and the highest dislocation density compared to the samples deformed at 50% and 70%. This refined microstructure significantly improves the mechanical properties, with the cryo-rolled sample deformed at 90% exhibiting the highest hardness (152 HV), tensile strength (1020 MPa), and yield strength (950 MPa), corresponding to an increase of 175.6%, 344.0%, and 466.5%, respectively. In addition, cryo-rolling at 90% showed a decrease in corrosion resistance, with the lowest corrosion rate observed at 90% deformation (5.97 mm/year).